Two telomerase-targeting Pt(ii) complexes of jatrorrhizine and berberine derivatives induce apoptosis in human bladder tumor cells. Issue 40 (2nd October 2019) - Qin, Qi-Pin; Wang, Zhen-Feng; Huang, Xiao-Ling; Tan, Ming-Xiong; Luo, Zhi-Hui; Wang, Shu-Long; Zou, Bi-Qun; Liang, Hong
Abstract : Two novel jatrorrhizine and berberine Pt(ii ) complexes Pt1 and Pt2 were first prepared as desirable luminescent agents for cellular applications and potent telomerase inhibitors, which also can induce T-24 tumor cell apoptosis. Abstract : Two novel Pt(ii ) complexes, [Pt(B-TFA)Cl]Cl (Pt1 ) and [Pt(J-TFA)Cl]Cl (Pt2 ) with jatrorrhizine and berberine derivatives (B-TFA and J-TFA ) were first prepared as desirable luminescent agents for cellular applications and potent telomerase inhibitors, which can induce bladder T-24 tumor cell apoptosis by targeting telomerase, together with induction of mitochondrial dysfunction, telomere DNA damage and cell-cycle arrest. Importantly, T-24 tumor inhibition rate (TIR) was 50.4% for Pt2, which was higher than that of Pt1 (26.4%) and cisplatin (37.1%). Taken together, all the results indicated that jatrorrhizine and berberine derivatives Pt1 and Pt2 show low toxicity and could be novel Pt-based anti-cancer drug candidates.